An Analysis on the Students Vocabulary Mastery - Waritsa Auliyah; Vitri Angraini Hardi; Lusi Marleni (Journal of Innovative and Creativity, 2025)
This research uses qualitative research. This research was conducted at the sixth grade of SD 006 Langgini. This research is aimed to determine the ability of English vocabulary mastery to sixth grade students in the first semester. This class is the youngest of the three classes in which class 6A consists of 29 students, class 6B consist of 26 students, and class 6C consist of 30 students. This study uses purposive sampling technique, the sample of this research is class 6C, which consist of 30 students. Based on the results finding of the research, it can be concluded that there are 13% of students who get the very good category in mastering English vocabulary. 13% of students get good category, 23% students get enough category, 34% of students get less category, and 17% students get bad category.